Au-Ag hybrid nanoparticle patterns of tunable size and density on glass and polymeric supports - Kruss, Sebastian; Spatz, Joachim P. (Langmuir, 2012)
This paper describes a method to pattern surfaces with Au-Ag hybrid nanoparticles. We used block copolymer micelle lithography of Au nanoparticles and electroless deposition of Ag. The combination of these two methods enables independent tuning of nanoparticle spacing and Ag-shell size. For this purpose, 8 nm large patterned Au nanoparticle seeds served as nuclei for the electroless deposition of silver that is based on a modified Tollens process with glucose. By adjusting the reaction conditions, specific growth of Ag on top of the Au seeds has been accomplished and analyzed by SEM, HRTEM, XEDS, and UV-vis spectroscopy. We could show that this versatile and green method is feasible on glass as well as on biomedical-relevant polymers like poly(ethylene glycol) hydrogels and amorphous Teflon. In conclusion, this method provides a new route to pattern glass and polymeric surfaces with Au-Ag hybrid nanoparticles. It will have many uses in applications such as surface enhanced Raman spectroscopy (SERS) or antimicrobial coatings for which hybrid nanoparticle density, size, and morphology are important.